Fostering innovation and competitiveness with fintech, regtech, and suptech - Boitan, Iustina Alina; Marchewka-Bartkowiak, Kamilla, 1973- (Advances in finance, accounting, and economics (AFAE) book series., 2021)
"This book addresses technologically innovative solutions and mechanisms from economic, financial, and legal perspectives"--